Elevated Serum Polybrominated Diphenyl Ethers and Thyroid-Stimulating Hormone Associated with Lymphocytic Micronuclei in Chinese Workers from an E-Waste Dismantling Site - Yuan, Jing; Chen, Lan; Chen, Duohong; Guo, Huan; Bi, Xinhui; Ju, Ying; Jiang, Pu; Shi, Jibin; Yu, Zhiqiang; Yang, Jin; Li, Liping; Jiang, Qi; et al. (Environmental science & technology, 2008)
In this study, we recruited 49 subjects from one village close to an electronic waste (e-waste) site (exposed group) and another located 50 km away from the e-waste site (control group). We found that serum levels of polybrominated diphenyl ethers (median PBDEs, 382 ng/g lipid weight; range, 77–8452 ng/g lipid weight) and thyroid-stimulating hormone (median TSH, 1.79 µIU/mL; range, 0.38–9.03 µIU/mL) and frequencies of micronucleated binucleated cells (MNed BNC; median, 5‰; range, 0–96‰) were significantly higher in the exposed group than in the control group (158 ng/g, range of 18–436 ng/g, and p < 0.05; 1.15 µIU/mL, range of 0.48–2.09, and p < 0.01; and 0‰, range of 0–5‰, and p < 0.01, respectively). A history of working with e-waste was significantly associated with increased MNed BNC frequencies (odds ratio (OR), 38.85; 95% confidence interval (CI) = 1–1358.71, p = 0.044), independent of years of local residence, a perceived risk factor. However, there was no association between PBDEs exposure and oxidative DNA damage. Therefore, the exposure to PBDEs at the e-waste site may have an effect on the levels of TSH and genetoxic damage among these workers, but this needs to be validated in large studies.